An Inexpensive, Portable Device for Point‐of‐Need Generation of Silver‐Nanoparticle Doped Cellulose Acetate Nanofibers for Advanced Wound Dressing. Issue 5 (24th March 2018) - Brako, Francis; Luo, Chaojie; Craig, Duncan Q. M.; Edirisinghe, Mohan
Abstract: This short communication describes the design and assembly of a new, miniaturized electrospinner to produce nanofibers at the site of need for drug delivery and wound dressing applications. The portable apparatus would eliminate the storage and transportation concerns with regards to the delicate nature of drug‐loaded nanofibers, thereby preserving product integrity at the site of use. Furthermore, the setup features a smaller size, a cheaper price, and components that are readily obtainable off‐the‐shelf, compared to those of available devices that are custom‐built and more expensive, making it desirable and accessible for other users in the field. As a proof‐of‐concept for wound care, the device is successfully used to electrospin three types of nanofibers comprised of pure cellulose acetate (CA), and CA respectively doped with 0.75 and 1.5 wt% silver nanoparticles. The miniaturized device is useful on account of the popularity of electrospinning as well as the potential to minimize wound infection due to the reduced manipulation of both the dressing and the wound from product generation to the point of need. Work is in progress to further develop the portable device and compare its product performance with traditional wound dressing materials for clinical translation. Abstract : A portable electrospinner made of smaller, cheaper, and off‐the‐shelf parts for drug delivery and wound dressing applications. Portable production at the site of use eliminates storage and transportation, thereby preserving the integrity of delicate drug‐loaded nanofibers while minimizing infection.